2010
DOI: 10.1164/rccm.201003-0481oc
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Hyponatremia in Patients with Acute Pulmonary Embolism

Abstract: Rationale: Although associated with adverse outcomes in other cardiopulmonary conditions, the prognostic value of hyponatremia, a marker of neurohormonal activation, in patients with acute pulmonary embolism (PE) is unknown. Objectives: To examine the associations between hyponatremia and mortality and hospital readmission rates for patients hospitalized with PE. Methods: We evaluated 13,728 patient discharges with a primary diagnosis of PE from 185 hospitals in Pennsylvania (January 2000 to November 2002). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 27 publications
5
44
2
2
Order By: Relevance
“…These include age, hyperlipidemia and serum hemoglobin. The current study not only confirms the acute prognostic importance of serum sodium in patients with acute PE [23], it also identifies that serum sodium during the index PE admission has important long-term prognostic influence for these patients. For every 1 mmol/l higher level of serum sodium on admission, there was a 3% lower risk for all-cause long-term mortality.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These include age, hyperlipidemia and serum hemoglobin. The current study not only confirms the acute prognostic importance of serum sodium in patients with acute PE [23], it also identifies that serum sodium during the index PE admission has important long-term prognostic influence for these patients. For every 1 mmol/l higher level of serum sodium on admission, there was a 3% lower risk for all-cause long-term mortality.…”
Section: Discussionsupporting
confidence: 75%
“…Hyponatremia is associated with adverse prognosis following acute coronary syndrome [19], patients with chronic heart failure [20], chronic renal failure on hemodialysis [21], and others [22]. Scherz et al [23] recently reported baseline hyponatremia to be a common phenomenon amongst patients presenting with acute PE and was an independent predictor of 30-day mortality. Including this easily obtainable biochemical parameter to the CCI score gave rise to a risk model that predicted in-hospital death with good discriminatory power (c statistic of 0.74, 95% CI 0.63-0.85; p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…The only published study to date on the influence of hyponatremia on readmission rates in the real-world was conducted by Scherz et al, who reported that the co-occurrence of hyponatremia in patients with acute pulmonary embolism, discharged from 185 hospitals in Pennsylvania, was independently associated with an increased readmission rate of 19.3%. 27 In the present study, hyponatremia was associated with an incremental increase ranging between 14% and 17% for hospital readmission for any cause. It was conducted on a patient population in which hyponatremia was resultant from many causes, and not all patients had a serious comorbid condition.…”
Section: Discussionmentioning
confidence: 46%
“…We found small but significant differences in laboratory parameters previously associated with morbidity in PE [12,13]. Patients with UPE had a slightly higher blood creatinine at PE diagnosis (1.16 ± 0.93 vs. 1.017± 0.44, respectively, p = 0.0341) and lower hemoglobin (11.7 ± 2.49 vs. 12.3 ± 1.75, respectively, p = 0.0089).…”
Section: Resultsmentioning
confidence: 59%